Why Indonesian MSMEs Should Go International : Economic and Social Benefits - Afifudin Afifudin; Sudarmiatin Sudarmiatin (Jurnal Bintang Manajemen, 2024)
Purpose: With a proper understanding of these opportunities and challenges, it is hoped that Indonesian MSMEs can be increasingly integrated into the global economy, thus providing great benefits to the Indonesian economy as a whole. The transformation of MSMEs to be more open to the international market is not only an option, but also a necessity to ensure economic and social sustainability and growth. Design/methodology/approach: The research uses mixed methods that combine qualitative and quantitative approaches, and the techniques used are in-depth interviews and focused discussions with the owner of CV Arjuna 99 (UMKM). Findings: The results of the study show that the success of CV Arjuna 99 in penetrating and maintaining the international market lies in continuous product innovation, high quality, and close partnerships with local farmers. By utilizing modern processing technology and continuing to develop variants of chips from natural ingredients, this business has succeeded in attracting interest from foreign markets, including countries such as Canada, Japan, Turkey, and Korea. This success not only has a positive impact on business growth, but also creates social benefits for local communities and employees.